Monolithic refractory and method for manufacturing monolithic refractory
The described composition of fire-resistant materials with carbon black-coated magnesia particles addresses erosion issues in conventional fireproofing by generating magnesium gas, enhancing resistance to molten slag and iron penetration.
Patent Information
- Application Number
- JP2023119992
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-24
- Publication Date
- 2025-02-05
Smart Images

Figure 2025017102000001_ABST
Abstract
Description
[Technical field]
[0001] The present application discloses a monolithic refractory and a method for making the monolithic refractory. [Background technology]
[0002] Various types of monolithic refractories are used as lining materials, coating agents, spraying materials, slinger materials, etc. for furnaces and their peripheral equipment. For example, Patent Document 1 discloses an alumina-spinel-silicon carbide-carbonaceous monolithic refractory for blast furnace troughs, in which the silicon carbide and spinel contents and particle sizes are within predetermined ranges. Patent Document 2 discloses an alumina-spinel-silicon carbide-carbonaceous monolithic refractory as a pouring material for blast furnace troughs, in which the contents of each component are within predetermined ranges. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 7-206532 [Patent Document 2] Japanese Patent Application Publication No. 5-339065 Summary of the Invention [Problem to be solved by the invention]
[0004] Monolithic refractories are corroded by contact with, for example, molten iron or molten slag. According to the findings of the present inventors, even a small amount of FeO is contained in the molten slag that contacts the monolithic refractory, the viscosity of the molten slag decreases, the contact angle between the molten slag and the monolithic refractory decreases, and the molten slag penetrates into the monolithic refractory, accelerating the erosion of the monolithic refractory. Conventional monolithic refractories still have room for improvement in terms of corrosion resistance to molten slag and molten iron. [Means for solving the problem]
[0005] The present application discloses the following aspects as means for solving the above problems. <Aspect 1> A monolithic refractory material, An alumina refractory raw material; a magnesia refractory raw material having a particle size of more than 0.5 mm and not more than 1 mm; A silicon carbide refractory raw material; Carbon black, one or both of graphite and pitch; Ultrafine silica powder and Alumina cement, A spinel refractory raw material; Including, The content of the alumina refractory raw material is 5% by mass or more and 40% by mass or less, The content of the magnesia refractory raw material is 5% by mass or more and 20% by mass or less, The content of the silicon carbide refractory raw material is 8% by mass or more and 15% by mass or less, The total content of the carbon black, the graphite, and the pitch is 3% by mass or more and 10% by mass or less, The content of the ultrafine silica powder is 1% by mass or more and 3% by mass or less, The content of the alumina cement is 1% by mass or more and 3% by mass or less, The content of the spinel refractory raw material is 30% by mass or more and 60% by mass or less, The magnesia refractory raw material is coated with the carbon black, and The content of the carbon black coating the magnesia refractory raw material is 1% by mass or more and 7% by mass or less. Monolithic refractories. <Aspect 2> A method for producing a monolithic refractory material, comprising the steps of: Coating a magnesia refractory raw material having a particle size of more than 0.5 mm and not more than 1 mm with carbon black; and The magnesia refractory raw material coated with carbon black, an alumina refractory raw material, a silicon carbide refractory raw material, one or both of graphite and pitch, ultrafine silica powder, alumina cement, and a spinel refractory raw material, The content of the alumina refractory raw material is 5% by mass or more and 40% by mass or less, The content of the magnesia refractory raw material is 5% by mass or more and 20% by mass or less, The content of the silicon carbide refractory raw material is 8% by mass or more and 15% by mass or less, The total content of the carbon black, the graphite, and the pitch is 3% by mass or more and 10% by mass or less, The content of the ultrafine silica powder is 1% by mass or more and 3% by mass or less, The content of the alumina cement is 1% by mass or more and 3% by mass or less, The content of the spinel refractory raw material is 30% by mass or more and 60% by mass or less, The content of the carbon black coating the magnesia refractory raw material is 1% by mass or more and 7% by mass or less, and mixing so that A method for producing a monolithic refractory material, comprising: Effect of the Invention
[0006] The monolithic refractory of the present disclosure has excellent corrosion resistance against molten iron and molten slag. [Brief description of the drawings]
[0007] [Figure 1] 1 is a schematic diagram showing an example of the morphology of a magnesia refractory raw material and carbon black in a monolithic refractory. [Diagram 2] 1 shows a schematic diagram of an example of a flow of a method for producing a monolithic refractory material. [Diagram 3] As an example of the application of the monolithic refractory, an example of the refractory lining structure of a blast furnace trough is shown generally. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, an embodiment of the monolithic refractory and the method for producing the same of the present disclosure will be described. However, the monolithic refractory and the method for producing the same of the present disclosure are not limited to the following embodiment.
[0009] 1. Monolithic refractories The amorphous refractory according to one embodiment includes an alumina refractory raw material, a magnesia refractory raw material having a particle size of more than 0.5 mm and not more than 1 mm, a silicon carbide refractory raw material, carbon black, one or both of graphite and pitch, ultrafine silica powder, alumina cement, and a spinel refractory raw material. Here, the content of the alumina refractory raw material is 5% by mass or more and 40% by mass or less. The content of the magnesia refractory raw material is 5% by mass or more and 20% by mass or less. The content of the silicon carbide refractory raw material is 8% by mass or more and 15% by mass or less. The total content of the carbon black, the graphite, and the pitch is 3% by mass or more and 10% by mass or less. The content of the ultrafine silica powder is 1% by mass or more and 3% by mass or less. The content of the alumina cement is 1% by mass or more and 3% by mass or less. The content of the spinel refractory raw material is 30% by mass or more and 60% by mass or less. The magnesia refractory raw material is coated with the carbon black, and the content of the carbon black coating the magnesia refractory raw material is 1% by mass or more and 7% by mass or less.
[0010] 1.1 Alumina refractory materials In the monolithic refractory according to one embodiment, the alumina-based refractory raw material may contain impurities together with alumina. For example, the alumina-based refractory raw material may contain one or both of calcium oxide and silicon dioxide together with alumina. The alumina-based refractory raw material may be, for example, at least one selected from sintered alumina, fused alumina, burnt alumina, bauxite, fused bauxite, and alumina shale. The alumina-based refractory raw material may contain, for example, 90% by mass or more and 100% by mass or less of alumina.
[0011] In the amorphous refractory according to one embodiment, the shape of the alumina refractory raw material may be a shape generally adopted as an amorphous refractory. The alumina refractory raw material may be, for example, particulate. The particle diameter of the alumina refractory raw material may be, for example, 0.1 mm or more and 10 mm or less. In the present application, the "particle diameter of the alumina refractory raw material" contained in the amorphous refractory is specified by observing the shape of the alumina refractory raw material contained in the amorphous refractory by SEM or the like. Specifically, a two-dimensional image of the amorphous refractory is obtained by SEM or the like, and the area circle equivalent diameter of the primary particles of the alumina refractory raw material contained in the two-dimensional image is obtained, and the area circle equivalent diameter is regarded as the "particle diameter of the alumina refractory raw material". Alternatively, in the raw material stage before the amorphous refractory is constituted, the particle diameter can be specified by mechanical sieving, microtrack method, or the like. The same applies to "particle diameter of magnesia refractory raw material," "particle diameter of silicon carbide refractory raw material," "particle diameter of carbon black," "particle diameter of graphite," "particle diameter of pitch," "particle diameter of ultrafine silica powder," and "particle diameter of spinel refractory raw material."
[0012] In the monolithic refractory according to one embodiment, the content of the alumina refractory raw material is 5% by mass or more and 40% by mass or less. This significantly improves the corrosion resistance of the monolithic refractory. The content of the alumina refractory raw material may be 5% by mass or more and 35% by mass or less, 5% by mass or more and 30% by mass or less, or 5% by mass or more and 25% by mass or less.
[0013] 1.2 Magnesia refractory raw materials with particle sizes of more than 0.5 mm and less than 1 mm In the monolithic refractory according to one embodiment, the magnesia-based refractory raw material having a particle size of more than 0.5 mm and not more than 1 mm may contain impurities together with magnesia. For example, the magnesia-based refractory raw material may contain one or both of calcium oxide and silicon dioxide together with magnesia. The magnesia-based refractory raw material may be one or both of sintered magnesia and electrofused magnesia. The magnesia-based refractory raw material may contain, for example, 90% by mass or more and 100% by mass or less of magnesia.
[0014] In the monolithic refractory according to one embodiment, the magnesia refractory raw material has a particle diameter of more than 0.5 mm and not more than 1 mm. By including a predetermined amount of the magnesia refractory raw material having such a particle diameter, the corrosion resistance of the monolithic refractory is improved. If the particle diameter of the magnesia refractory raw material is too small, the monolithic refractory may expand and crack due to the reaction between magnesia and water during the drying process when the monolithic refractory is applied, which may cause the magnesia to react with water to generate magnesium hydroxide (MgO+H2O→Mg(OH)2). On the other hand, if the particle diameter of the magnesia refractory raw material is too large, the magnesia-carbon reaction described below may not proceed sufficiently, and the effect of improving the corrosion resistance may decrease.
[0015] In the monolithic refractory according to one embodiment, the content of the magnesia refractory raw material having a particle size of more than 0.5 mm and not more than 1 mm is 5% by mass or more and not more than 20% by mass. This significantly improves the corrosion resistance and heat spalling resistance of the monolithic refractory. The content of the magnesia refractory raw material having a particle size of more than 0.5 mm and not more than 1 mm may be 7% by mass or more and not more than 20% by mass, 9% by mass or more and not more than 20% by mass, or 11% by mass or more and not more than 20% by mass. In the monolithic refractory according to one embodiment, the magnesia refractory raw material having a particle size of 0.5 mm or less or more than 1 mm may be unavoidably present, but it is preferable that the content is as small as possible (for example, less than 1% by mass).
[0016] 1.3 Silicon carbide refractory materials In the monolithic refractory according to an embodiment, the silicon carbide refractory raw material may contain impurities in addition to silicon carbide. For example, the silicon carbide refractory raw material may contain impurities such as carbon and / or iron in addition to silicon carbide. The silicon carbide refractory raw material may contain, for example, 90% by mass or more and 100% by mass or less of silicon carbide.
[0017] In the amorphous refractory according to one embodiment, the shape of the silicon carbide refractory raw material may be a shape generally adopted as an amorphous refractory. The silicon carbide refractory raw material may be, for example, particulate. The particle size of the silicon carbide refractory raw material may be, for example, 45 μm or more and 1 mm or less.
[0018] In the monolithic refractory according to one embodiment, the content of the silicon carbide refractory raw material is 8% by mass or more and 15% by mass or less. This significantly improves the corrosion resistance of the monolithic refractory. The content of the silicon carbide refractory raw material may be 9% by mass or more and 15% by mass or less, 11% by mass or more and 15% by mass or less, or 13% by mass or more and 15% by mass or less.
[0019] 1.4 Carbon black In the monolithic refractory according to one embodiment, at least a part of the magnesia refractory raw material is coated with carbon black. For example, as shown in FIG. 1, carbon black 20 may be attached to the surface of a particle 10 of the magnesia refractory raw material to form a composite particle 30. By coating the magnesia refractory raw material with carbon black, when the monolithic refractory is used, magnesia and carbon black undergo a thermal decomposition reaction (MgO+C→Mg↑+CO↑) to generate magnesium gas in the monolithic refractory. The magnesium gas generated in the monolithic refractory increases the pressure in the monolithic refractory, making it difficult for molten iron, molten slag, etc. to penetrate into the monolithic refractory. Even if the molten slag contains FeO and is in a state where it is easily permeated into the monolithic refractory, the magnesium gas suppresses the permeation of the molten slag, and the corrosion resistance of the monolithic refractory is significantly improved. Such an effect is remarkable when the magnesia refractory raw material is coated with carbon black. When the magnesia refractory raw material is coated with graphite or pitch instead of carbon black, the contact and reactivity of the carbon material with the magnesia refractory raw material is not sufficiently ensured, and the magnesia-carbon reaction tends to be difficult to occur.
[0020] Carbon black is generally in the form of particles. The particle size of the carbon black may be, for example, less than 1 μm. As shown in FIG. 1, in one embodiment, the particle size of the carbon black 20 is preferably smaller than the particle size of the magnesia-based refractory raw material 10.
[0021] In the monolithic refractory according to one embodiment, the content of carbon black coating the magnesia refractory raw material is 1% by mass or more and 7% by mass or less. This allows the magnesia-carbon reaction to occur appropriately, and the corrosion resistance of the monolithic refractory is significantly improved. The content of carbon black coating the magnesia refractory raw material may be 2% by mass or more and 7% by mass or less, 3% by mass or more and 7% by mass or less, 4% by mass or more and 7% by mass or less, or 5% by mass or more and 7% by mass or less.
[0022] In one embodiment, the content of the carbon black that coats the magnesia refractory raw material in the carbon black contained in the monolithic refractory may be greater than the content of the carbon black that exists independently of the magnesia refractory raw material. This more significantly improves the corrosion resistance of the monolithic refractory. In the monolithic refractory according to one embodiment, the content of the carbon black that does not coat the magnesia refractory raw material and exists independently of the magnesia refractory raw material may be, for example, 0% by mass or more and 1% by mass or less.
[0023] In the monolithic refractory according to one embodiment, at least a part of the surface of the magnesia refractory raw material may be coated with carbon black. In particular, by coating 50% or more of the surface of the magnesia refractory raw material with carbon black, particularly 70% or more of the surface of the magnesia refractory raw material with carbon black, a higher effect can be expected. Note that, in the monolithic refractory according to one embodiment, the presence of a magnesia refractory raw material that is not coated with carbon black is not excluded, and such a magnesia refractory raw material may be included within a range that can solve the problem.
[0024] 1.5 Graphite and / or pitch As described above, the monolithic refractory according to one embodiment contains carbon black that coats the magnesia refractory raw material. In addition, by containing other carbonaceous raw materials in the monolithic refractory together with carbon black, the monolithic refractory is less likely to be wetted by molten slag, and the corrosion resistance of the monolithic refractory is more significantly improved. In this regard, the monolithic refractory according to one embodiment may contain one or both of graphite and pitch as carbonaceous raw materials other than carbon black. The monolithic refractory according to one embodiment may be any of a monolithic refractory containing graphite, a monolithic refractory containing pitch, and a monolithic refractory containing graphite and pitch, but in particular, when it is a monolithic refractory containing graphite or a monolithic refractory containing graphite and pitch, it is easy to exhibit more excellent performance.
[0025] In the monolithic refractory according to an embodiment, the graphite may be, for example, particulate. The particle size of the graphite may be, for example, less than 250 μm. In the monolithic refractory according to an embodiment, the pitch may be, for example, particulate. The particle size of the pitch may be, for example, less than 75 μm.
[0026] In the monolithic refractory according to one embodiment, the graphite content may be, for example, 0% by mass or more and 5% by mass or less, 0% by mass or more and 4% by mass or less, or 1% by mass or more and 3% by mass or less. In addition, in the monolithic refractory according to one embodiment, the pitch content may be, for example, 0% by mass or more and 5% by mass or less, 0% by mass or more and 4% by mass or less, or 0% by mass or more and 3% by mass or less.
[0027] 1.6 Ultrafine Silica Powder In the monolithic refractory according to one embodiment, the ultrafine silica powder may contain impurities in addition to silica. For example, the ultrafine silica powder may contain at least one of magnesium oxide, sulfur trioxide, and calcium oxide in addition to silica. For example, the ultrafine silica powder may contain silica in an amount of 85% by mass or more and 100% by mass or less.
[0028] In the monolithic refractory according to one embodiment, the ultrafine silica powder may be in a powder form generally used for monolithic refractories. The particle size of the ultrafine silica powder may be, for example, less than 0.1 μm.
[0029] In the monolithic refractory according to one embodiment, the content of ultrafine silica powder is 1% by mass or more and 3% by mass or less. This significantly improves the corrosion resistance of the monolithic refractory. The content of ultrafine silica powder may be 2% by mass or more and 3% by mass or less.
[0030] 1.7 Alumina cement In the unshaped refractory according to one embodiment, the alumina cement can function as a binder for binding the above-mentioned components together. The alumina cement may be any known alumina cement used as an unshaped refractory.
[0031] In the monolithic refractory according to one embodiment, the content of alumina cement is 1% by mass or more and 3% by mass or less. This significantly improves the heat resistance and heat spalling resistance of the monolithic refractory. The content of alumina cement may be 2% by mass or more and 3% by mass or less.
[0032] 1.8 Spinel refractory materials In the monolithic refractory according to an embodiment, the spinel refractory raw material may contain impurities together with the spinel. For example, the spinel refractory raw material may contain at least one of silicon dioxide, calcium oxide, and sodium oxide together with the spinel. The spinel refractory raw material may contain, for example, 90% by mass or more and 100% by mass or less of the spinel.
[0033] In the monolithic refractory according to an embodiment, the shape of the spinel refractory raw material may be a shape generally adopted for monolithic refractories. The spinel refractory raw material may be, for example, particulate. The particle diameter of the spinel refractory raw material may be, for example, 75 μm or more and 3 mm or less.
[0034] In the monolithic refractory according to one embodiment, the content of the spinel refractory raw material is 30% by mass or more and 60% by mass or less. This significantly improves the corrosion resistance of the monolithic refractory. The content of the spinel refractory raw material may be 40% by mass or more and 48% by mass or less.
[0035] 1.9 Other Ingredients The monolithic refractory according to one embodiment may contain other components in addition to the above-mentioned components. Examples of the other components include at least one additive selected from a resin (organic binder), a dispersant, an anti-splintering agent, etc. In the monolithic refractory according to one embodiment, the content of the other components may be, for example, 0% by mass or more and 1% by mass or less.
[0036] 1.10 Supplementary Information The composition of the monolithic refractory can be determined by observing and analyzing it using a chemical analysis method for carbon and silicon carbide-containing refractories described in JIS R 2011, a scanning electron microscope (SEM), an electron beam μ analyzer (EPMA), or the like. XRD, etc. may be used in combination as necessary. Alternatively, the composition of the monolithic refractory can be determined by the charging ratio of the raw materials.
[0037] 2. Manufacturing method of monolithic refractories The above-mentioned monolithic refractory can be manufactured, for example, by the following method. As shown in FIG. 2, the manufacturing method of the monolithic refractory 100 according to one embodiment includes the following steps: A magnesia refractory raw material 10 having a particle size of more than 0.5 mm and not more than 1 mm is coated with carbon black 20; and A magnesia refractory raw material 10 coated with carbon black 20, an alumina refractory raw material 40, a silicon carbide refractory raw material 50, one or both of graphite 61 and pitch 62, ultrafine silica powder 70, an alumina cement 80, and a spinel refractory raw material 90, The content of the alumina refractory raw material 40 is 5% by mass or more and 40% by mass or less, The content of magnesia refractory raw material 10 is 5% by mass or more and 20% by mass or less, The content of silicon carbide refractory raw material 50 is 8% by mass or more and 15% by mass or less, The total content of carbon black 20, graphite 61 and pitch 62 is 3% by mass or more and 10% by mass or less, The content of ultrafine silica powder 70 is 1% by mass or more and 3% by mass or less, The content of alumina cement 80 is 1% by mass or more and 3% by mass or less, The content of spinel refractory raw material 90 is 30% by mass or more and 60% by mass or less, The content of carbon black 20 covering the magnesia refractory raw material 10 is 1% by mass or more and 7% by mass or less, and mixing so that Includes.
[0038] 2.1 Coating of magnesia refractory raw materials In one embodiment of the method for producing a monolithic refractory, a magnesia-based refractory raw material having a particle size of more than 0.5 mm and not more than 1 mm is coated with carbon black. The method for coating the magnesia-based refractory raw material with carbon black is not particularly limited. For example, the magnesia-based refractory raw material can be coated with carbon black by any of the following methods: (1) dry mixing, (2) wet mixing, and (3) immersion stirring. (1) In the dry mixing, for example, the magnesia-based refractory raw material and carbon black are loaded into various dry mixing devices such as a mixer and mixed, so that the carbon black is adhered to the surface of the magnesia-based refractory raw material by physical bonding force. (2) In the wet mixing, for example, the magnesia refractory raw material and the carbon black are loaded into various wet mixing devices such as a mixer together with a solvent and mixed, so that the carbon black is attached to the surface of the magnesia refractory raw material by physical or chemical bonding force. As the solvent in this case, for example, various organic solvents can be used. In this case, various resins as organic binders may be mixed together with the solvent. Specifically, the magnesia refractory raw material and the carbon black may be bonded to each other via the resin by wet mixing the magnesia refractory raw material and the carbon black together with a resin solution or resin dispersion. In this case, the resin may be at least one selected from, for example, an epoxy resin, a furan resin, and a phenol resin. (3) In the immersion stirring method, for example, a slurry in which carbon black is dispersed in a solvent is prepared, and the magnesia-based refractory raw material is immersed in the slurry and stirred, so that the carbon black adheres to the surface of the magnesia-based refractory raw material by physical or chemical bonding forces.
[0039] The amount (mass) of carbon black coated on the magnesia refractory raw material can be determined by measuring the difference between the mass of the magnesia refractory raw material before the coating treatment and the mass of the composite particles after the coating treatment and drying at 110°C to 600°C. Whether the magnesia refractory raw material is coated with carbon black can be confirmed by SEM and EPMA. That is, by using two devices, SEM and EPMA, the presence or absence of a coating on the surface of the magnesia refractory raw material can be confirmed, and whether the coating is carbon black can be confirmed by morphological analysis, composition analysis, etc. of the coating.
[0040] 2.2 Mixing of each component When the magnesia refractory raw material and carbon black are mixed, if the alumina refractory raw material, silicon carbide refractory raw material, graphite, pitch, ultrafine silica powder, alumina cement, and spinel refractory raw material are coexistent, it becomes difficult to adequately coat the magnesia refractory raw material with carbon black. In this regard, when the magnesia refractory raw material and carbon black are mixed, it is better not to allow the alumina refractory raw material, silicon carbide refractory raw material, graphite, pitch, ultrafine silica powder, alumina cement, and spinel refractory raw material to coexist. That is, as shown in Fig. 2, the magnesia refractory raw material 10 is coated with carbon black 20 to obtain composite particles 30, and then the composite particles 30, the alumina refractory raw material 40, the silicon carbide refractory raw material 50, one or both of graphite 61 and pitch 62, ultrafine silica powder 70, alumina cement 80, and the spinel refractory raw material 90 are mixed to obtain an amorphous refractory material 100 containing the composite particles 30. In this case, the mixing of each component is preferably performed in a dry manner, for example. For example, a twin blade mixer or an omni mixer can be used as a dry mixer.
[0041] 3. Uses of unshaped refractories The above-mentioned monolithic refractory can be used as a lining material, a coating agent, a spraying material, a slinger material, and the like for furnaces and their peripheral equipment. As described above, when the monolithic refractory of the present disclosure is used, the magnesium gas is generated by the thermal decomposition reaction between magnesia and carbon, thereby suppressing the penetration of molten iron and molten slag into the monolithic refractory, and excellent corrosion resistance is exhibited. In this respect, the monolithic refractory of one embodiment is useful, for example, as a lining material for a blast furnace runner. Specifically, as shown in FIG. 3, in a refractory lining structure 200 for a blast furnace runner, the metal line portion 201 of the metal line portion 201 and the slag line portion 202 on the inner wall surface of the blast furnace runner may be lined with the monolithic refractory of the present disclosure. The metal line portion 201 on the inner wall surface of the blast furnace runner may come into contact with the molten iron 210 and the molten slag 220 floating (flowing) on the molten iron 210. The molten slag 220 near the molten iron 210 contains FeO and is considered to be in a state where it is easy to permeate the monolithic refractory. That is, it is considered that the molten slag 220 is easy to permeate, particularly, the monolithic refractory of the metal line portion 201. In contrast, when the metal line portion 201 is lined with the monolithic refractory of the present disclosure, the presence of the above-mentioned magnesium gas can suppress the permeation of the molten slag into the monolithic refractory. The upper end of the metal line portion 201 may be located above the boundary position between the molten iron 210 and the molten slag 220. The lining of the monolithic refractory on the inner wall surface of the blast furnace trough is performed, for example, by the following procedure. That is, the monolithic refractory of the present disclosure is mixed with water, poured into a formwork, and dried at a temperature of 800°C or less.
[0042] 4.Effects As described above, the monolithic refractory of the present disclosure generates magnesium gas by causing a magnesia-carbon reaction during use, making it difficult for molten iron or molten slag to penetrate, and can exhibit excellent corrosion resistance against molten iron or molten slag. The monolithic refractory of the present disclosure can be suitably used, in particular, as a lining material for a portion that comes into contact with specific molten iron (molten pig iron) and molten slag, such as a blast furnace trough. EXAMPLES
[0043] The present invention will be further described below with reference to examples, but the present invention is not limited to the following examples. The present invention can adopt various conditions as long as it does not deviate from the gist of the invention and achieves its object.
[0044] 1. Preparation of unshaped refractory Monolithic refractories having various compositions and properties were prepared.
[0045] 1.1 Examples 1 to 5 and Comparative Examples 3 to 5 A magnesia refractory raw material (particle size: more than 0.5 mm and less than 1 mm, magnesia purity: 98%) was mixed with carbon black (particle size: average 0.1 μm), and the magnesia refractory raw material was coated with carbon black by wet mixing to obtain composite particles. The amount of carbon black coated on the magnesia refractory raw material was changed by changing the mixing ratio of carbon black to the magnesia refractory raw material. In this example and comparative example, substantially the entire amount of the mixed carbon black was attached to the magnesia refractory raw material.
[0046] The obtained composite particles, an alumina refractory raw material (particle diameter: 1 μm to 8 mm, alumina purity: 99%), a silicon carbide refractory raw material (particle diameter: 75 μm to 1 mm, silicon carbide purity: 90%), one or both of graphite (particle diameter: less than 250 μm) and pitch (particle diameter: less than 75 μm), ultrafine silica powder (particle diameter: average 0.1 μm), alumina cement, and a spinel refractory raw material (particle diameter: 75 μm to 3 mm) were mixed in a dry state to obtain an amorphous refractory for evaluation. When observed with SEM and EPMA, there was no slippage of carbon black from the magnesia refractory raw material in the amorphous refractory, and substantially the entire amount of the mixed carbon black covered the surface of the magnesia refractory raw material. The composition of the obtained amorphous refractory is shown in Table 1 below.
[0047] 1.2 Comparative Example 1 In the case of the monolithic refractory, the magnesia refractory raw material was not mixed, and the alumina refractory raw material, the silicon carbide refractory raw material, the carbon black, the graphite, the ultrafine silica powder, the alumina cement, and the spinel refractory raw material were mixed in a dry state to obtain a monolithic refractory for evaluation. The composition of the obtained monolithic refractory is shown in Table 1 below.
[0048] 1.3 Comparative Example 2 The magnesia refractory raw material was not coated with carbon black in advance, and the alumina refractory raw material, the magnesia refractory raw material, the silicon carbide refractory raw material, the carbon black, the graphite, the pitch, the ultrafine silica powder, the alumina cement, and the spinel refractory raw material were mixed in a dry state according to the composition shown in Table 1 below to obtain a monolithic refractory for evaluation. The composition of the obtained monolithic refractory is shown in Table 1 below.
[0049] 1.4 Comparative Example 6 The magnesia refractory raw material was coated with graphite instead of carbon black to obtain composite particles, and then the composite particles were mixed with the alumina refractory raw material, the silicon carbide refractory raw material, the carbon black, the pitch, the ultrafine silica powder, the alumina cement, and the spinel refractory raw material in a dry state to obtain a monolithic refractory for evaluation. The composition of the obtained monolithic refractory is shown in Table 1 below.
[0050] 2.Corrosion resistance evaluation The corrosion resistance was evaluated by a lining corrosion test method using a high-frequency induction furnace. After melting pig iron at 1600°C, granulated blast furnace slag was charged, and after the granulated blast furnace slag was completely melted, it was held for 3 hours to corrode the sample. To evaluate the corrosion resistance, the test piece was cut after the test was completed, and the maximum amount of corrosion loss was measured, and the amount of corrosion loss in Comparative Example 1 was set to 100 and expressed as an index. The smaller the value, the better the corrosion resistance.
[0051] 3. Evaluation of refractory wear rate in actual equipment The following evaluation was carried out assuming a monolithic refractory lining a metal line portion 201 of a refractory lining structure 200 of a blast furnace trough as shown in FIG.
[0052] The metal line portion of the inner wall surface of the blast furnace runner was lined with the monolithic refractories according to the above-mentioned Examples and Comparative Examples. Thereafter, the wear rate of the refractory of the blast furnace runner was measured by measuring the width of the runner after 10,000 tons of molten pig iron had passed through it and the width of the runner before the molten pig iron passed through it. In this example, the wear rate (mm / kt) when 1,000 tons of molten pig iron passed through the blast furnace runner was used as an index of evaluation. According to the knowledge of the present inventor, in the metal line portion of the inner wall surface of the blast furnace runner, wear of the refractory is likely to occur near the boundary between the molten pig iron and the molten slag, and the wear rate is significantly high. This is considered to be because, in the metal line portion near the boundary between the molten pig iron and the molten slag, the molten slag is likely to penetrate the monolithic refractory. In this example, the wear rate of the metal line portion was evaluated as the wear rate of the most worn part near the boundary.
[0053] 4. Evaluation Results The composition of the monolithic refractory, the corrosion resistance of the monolithic refractory, and the wear rate of the monolithic refractory are summarized in Table 1 below. The corrosion resistance of the monolithic refractory is indexed based on the corrosion resistance of the monolithic refractory according to Comparative Example 1 (100). In Table 1 below, the smaller the value for corrosion resistance, the more excellent the corrosion resistance.
[0054] [Table 1]
[0055] The results shown in Table 1 reveal the following:
[0056] In the case where the monolithic refractory does not contain the magnesia refractory raw material coated with carbon black as in Comparative Example 1, the monolithic refractory is easily permeated with molten slag during use, resulting in a high wear rate of the inactive refractory.
[0057] When the magnesia refractory raw material and carbon black are added separately and mixed in the monolithic refractory as in Comparative Example 2, no improvement in corrosion resistance is obtained compared to Comparative Example 1. In Comparative Example 2, it is considered that the amount of carbon black in contact with the magnesia refractory raw material is very small, and the thermal decomposition reaction between the magnesia refractory raw material and the carbon black hardly occurs when the monolithic refractory is used.
[0058] Even if the magnesia refractory raw material coated with carbon black is mixed in the monolithic refractory as in Comparative Examples 3 and 4, if the mixed amount is too small or too large, the corrosion resistance is not improved as compared to Comparative Example 1. If the mixed amount is too small, it is considered that the thermal decomposition reaction between the magnesia refractory raw material and the carbon black cannot be sufficiently caused when the monolithic refractory is used. On the other hand, if the mixed amount is too large, the magnesia becomes excessive, and it is considered that the performance balance of the refractory as a whole is poor.
[0059] Even if a magnesia refractory raw material coated with carbon black is mixed in an amorphous refractory as in Comparative Example 5, if the amount of carbon black coating the magnesia refractory raw material is too large, no improvement in corrosion resistance can be obtained compared to Comparative Example 1. If the amount of carbon black coating is too large, the magnesia refractory raw material and the carbon black react excessively when the amorphous refractory is used, causing excessive disappearance of the magnesia refractory raw material and the generation of voids, and it is considered that the effect of improving corrosion resistance by the magnesia refractory raw material itself becomes insufficient.
[0060] Even if a magnesia refractory raw material coated with graphite is mixed in a monolithic refractory as in Comparative Example 6, no improvement in corrosion resistance is obtained compared to Comparative Example 1. It is considered that graphite is less reactive with the magnesia refractory raw material than carbon black, and thus the thermal decomposition reaction of the magnesia refractory raw material cannot be sufficiently caused.
[0061] In contrast, as in Examples 1 to 5, by mixing an appropriate amount of magnesia refractory raw material coated with a predetermined amount of carbon black in the monolithic refractory, the corrosion resistance is significantly improved compared to Comparative Example 1. It is considered that, when the monolithic refractory of Examples 1 to 5 is used, magnesia and carbon black undergo a thermal decomposition reaction (MgO+C→Mg↑+CO↑) to generate magnesium gas within the monolithic refractory, and that the magnesium gas generated within the monolithic refractory increases the pressure within the monolithic refractory, making it difficult for molten iron, molten slag, etc. to penetrate into the monolithic refractory. As a result, it is considered that the corrosion resistance of the monolithic refractory is significantly improved.
[0062] From the above results, it can be said that a monolithic refractory satisfying all of the following requirements (A) to (I) has excellent corrosion resistance against molten slag and molten iron. (A) The content of the alumina refractory raw material is 5% by mass or more and 40% by mass or less. (B) The content of the magnesia refractory raw material is 5% by mass or more and 20% by mass or less. (C) The content of the silicon carbide refractory raw material is 8% by mass or more and 15% by mass or less. (D) The total content of carbon black, graphite, and pitch is 3% by mass or more and 10% by mass or less. (E) The content of ultrafine silica powder is 1% by mass or more and 3% by mass or less. (F) The alumina cement content is 1% by mass or more and 3% by mass or less. (G) The content of the spinel refractory raw material is 30% by mass or more and 60% by mass or less. (H) Magnesia refractory raw material is coated with carbon black. (I) The content of carbon black coating the magnesia refractory raw material is 1% by mass or more and 7% by mass or less. [Explanation of symbols]
[0063] 100 Monolithic refractories 10. Magnesia refractory materials 20 Carbon Black 30 Composite particles 40 Alumina refractory materials 50 Silicon carbide refractory materials 61 Graphite 62 pitch 70 Ultrafine Silica Powder 80 Alumina cement 90 Spinel refractory materials 200 Refractory lining structure of blast furnace trough 201 Metal line part on the inner wall of the blast furnace trough 202 Slag line on the inner wall of the blast furnace trough 210 Molten Iron 220 Molten Slag
Claims
1. A monolithic refractory material, An alumina refractory raw material; A magnesia refractory raw material having a particle size of more than 0.5 mm and not more than 1 mm; A silicon carbide refractory raw material; Carbon black, one or both of graphite and pitch; Ultrafine silica powder and Alumina cement, A spinel refractory raw material; Including, The content of the alumina refractory raw material is 5% by mass or more and 40% by mass or less, The content of the magnesia refractory raw material is 5% by mass or more and 20% by mass or less, The content of the silicon carbide refractory raw material is 8% by mass or more and 15% by mass or less, The total content of the carbon black, the graphite, and the pitch is 3% by mass or more and 10% by mass or less, The content of the ultrafine silica powder is 1% by mass or more and 3% by mass or less, The content of the alumina cement is 1% by mass or more and 3% by mass or less, The content of the spinel refractory raw material is 30% by mass or more and 60% by mass or less, The magnesia refractory raw material is coated with the carbon black, and The content of the carbon black coating the magnesia refractory raw material is 1% by mass or more and 7% by mass or less. Monolithic refractories.
2. A method for producing a monolithic refractory material, comprising the steps of: Coating a magnesia refractory raw material having a particle size of more than 0.5 mm and not more than 1 mm with carbon black; and The magnesia refractory raw material coated with carbon black, an alumina refractory raw material, a silicon carbide refractory raw material, one or both of graphite and pitch, ultrafine silica powder, alumina cement, and a spinel refractory raw material, The content of the alumina refractory raw material is 5% by mass or more and 40% by mass or less, The content of the magnesia refractory raw material is 5% by mass or more and 20% by mass or less, The content of the silicon carbide refractory raw material is 8% by mass or more and 15% by mass or less, The total content of the carbon black, the graphite, and the pitch is 3% by mass or more and 10% by mass or less, The content of the ultrafine silica powder is 1% by mass or more and 3% by mass or less, The content of the alumina cement is 1% by mass or more and 3% by mass or less, The content of the spinel refractory raw material is 30% by mass or more and 60% by mass or less, The content of the carbon black coating the magnesia refractory raw material is 1% by mass or more and 7% by mass or less, and mixing so that A method for producing a monolithic refractory material, comprising:
Citation Information
Patent Citations
Casting material for blast furnace trough
JP1993339065A
Monolithic refractory
JP1995206532A